Herbal Preparation (Bromelain, Papain, Curcuma, Black Pepper) Enhances Mineralization and Reduces Glucocorticoid-Induced Osteoporosis in Zebrafish - Marta Carnovali; Gina Ramoni; Giuseppe Banfi; Massimo Mariotti (MDPI AG, 2021)
Natural foods with antioxidant properties, such as curcuma, papain, bromelain and black pepper, have been indicated as a potential natural therapeutic approach against osteoporosis. Zebrafish are an excellent animal model to study the effects of herbal preparations on osteogenesis and bone metabolism, both in physiological and in pathological conditions. Our study was aimed at evaluating whether curcuma-bromelain-papain-pepper herbal preparation (CHP) administered in embryos and adult fish is capable of promoting bone wellness in physiological and osteoporotic conditions. The effect of CHP has been studied in embryonic osteogenesis and glucocorticoid-induced osteoporosis (GIOP) in an adult fish model in which drug treatment induces a bone-loss phenotype in adult scales very similar to that which characterizes the bones of human patients. CHP prevented the onset of the osteoporotic phenotype in the scales of GIOP in adult zebrafish, with the osteoblastic and osteoclastic metabolic activity maintaining unaltered. CHP is also able to attenuate an already established GIOP phenotype, even if the alteration is in an advanced phase, partially restoring the normal balance of the bone markers alkaline phosphatase (ALP) and tartrate-resistant acid phosphatase (TRAP) and stimulating anabolic reparative processes. The results obtained indicated CHP as a potential integrative antioxidant therapy in human bone-loss diseases.